Reproducing neglect in the place of care: Normalised violence within Cape Town Midwifery Obstetric Units. Issue 1 (2nd January 2020) - Dutton, Jessica; Knight, Lucia
Abstract: Access to quality maternal health care within South Africa is strongly determined by where a woman lives and her socioeconomic positioning. Through an analysis of experiences shared by nurses and midwives working within Midwifery Obstetric Units (MOUs) within Cape Town, this article considers how the South African health system maintains and reproduces gendered inequalities. The ways in which such inequalities materialise within an MOU are vast; for this article we focus on the issue of patient neglect. We approach neglect as a form of reproductive governance, and resource shortage as a form of violence, and the ways in which both devalue women's reproductive labour. Resistance takes the form of kindness, and is always under duress within a system that is predicated on inequality.